Penentuan Prioritas Strategi Pengelolaan K3 Proyek Pemasangan Pipa Gas Menggunakan Pendekatan Metode AHP - Rosita Robi Agustini; Dino Rimantho (Department Industrial Engineering, University of Muhammadiyah Malang, 2018)
The pipeline is an immobile transport medium that functions to distribute liquids and gases. The pipeline installation project is one of the Engineering Procurement and Construction (EPC) projects that has the potential for accident and occupational safety risks. The purpose of this research is to determine the priority of work accident management strategies gas pipeline by applying the AHP method. Brainstorming and pair-wise comparison approaches were conducted by experts. A total of three experts are used as key informants in assessing paired comparisons. The results show that there are four main factors that could potentially result in the risk of working accidents such as humans, machines, methods, and materials. Furthermore, based on the analysis result shows that human factor is the highest priority and environmental factor as the lowest priority. The AHP method application in this study indicates that this method can be used to determine the priority of each criterion and sub-criteria on the health and safety management strategy of the gas pipeline installation project. The implication of this in the application of AHP in other issues required more in-depth review related to the criteria and sub-criteria that are used to obtain more comprehensive results.